2018
DOI: 10.1080/02770903.2018.1466311
|View full text |Cite
|
Sign up to set email alerts
|

Reduced longitudinal cardiac strain in asthma patients

Abstract: Allergic asthma, especially severe asthma is associated with subclinical impaired left and right ventricular function as determined by speckle-tracking analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…These findings appear to be consistent with recent studies in adult population. In line with these observations, previous studies have reported various cardiac abnormalities in asthmatic patients such as an increase in indexed LV mass ( Sun et al, 2017 ) and a significantly reduced left and right ventricular strain values in severe and mild-to-moderate asthma ( Tulet et al, 2019 ). More recently, the BADA study-ECO has provided further evidence supporting the existence of significant subclinical cardiac involvement in asthma ( Di Raimondo et al, 2022 ).…”
Section: Introductionsupporting
confidence: 69%
“…These findings appear to be consistent with recent studies in adult population. In line with these observations, previous studies have reported various cardiac abnormalities in asthmatic patients such as an increase in indexed LV mass ( Sun et al, 2017 ) and a significantly reduced left and right ventricular strain values in severe and mild-to-moderate asthma ( Tulet et al, 2019 ). More recently, the BADA study-ECO has provided further evidence supporting the existence of significant subclinical cardiac involvement in asthma ( Di Raimondo et al, 2022 ).…”
Section: Introductionsupporting
confidence: 69%
“…In our study, the LV systolic function was preserved in the patient group. Ozdemir et al reported similar findings regarding EF and S′ velocity at the mitral annulus, wh ile Tuleta et al reported diminished LV longitudinal strain in patients with severe and mild to moderate asthma. This is in contrast to our patients who mostly had mild asthma.…”
Section: Discussionmentioning
confidence: 69%
“…In the current study, LV function was preserved in the asthmatic group by conventional and speckle tracking imaging. Abdelmohsen et al 6 reported similar results, while Tuleta et al 11 reported diminished LV GLS in moderate to severe asthma.…”
Section: Discussionmentioning
confidence: 81%